Constitution of India - Lal, J. (Allahabad, 1991)
This thoroughly revised and enlarged Third Edition has been released to fill in the gap for a good, small book on the CONSTITUTION OF INDIA. This handy book has been consistently improved upon edition after edition. The present edition is supported by latest Supreme Court decisions that are found invari ably quoted throughout the text of the book. In addition the following appendices inclusive of the object and reasons of each one of the sixty-first constitutional Amendment Acts which are essentially required by the readers for interpretation of the constitutional provisions and the amendments which lay scattered in several volumes of Gazettes of India have been collected and arranged amendment-wise for ready reference.
Keywords: Lal